2018
DOI: 10.1186/s13014-018-1154-3
|View full text |Cite
|
Sign up to set email alerts
|

Does baseline [18F] FDG-PET/CT correlate with tumor staging, response after neoadjuvant chemoradiotherapy, and prognosis in patients with rectal cancer?

Abstract: Background[18F] fluorodeoxyglucose positron emission tomography/computed tomography ([18F] FDG-PET/CT) may be used for tumor staging and prognosis in several tumors but its role in rectal cancer is still debated. The aim of the present study was to assess the correlation of baseline [18F] FDG-PET parameters with tumor staging, tumor response (tumor regression grade (TRG)), and outcome in a series of patients affected by locally advanced rectal cancer (LARC) treated with neoadjuvant chemoradiotherapy (CRT).Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In the present study, FDG uptake by the primary CRC was not associated with OS in the univariate analysis ( p = 0.965). Some previous studies have demonstrated that SUV max of the primary tumor may affect CRC prognosis 26 , 27 ; other studies have reported that PET/CT parameters are not associated with either disease-free survival or OS 28 30 . These discrepancies in findings may be because of the variability in tumor SUV measurements, confounded by tumor-associated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, FDG uptake by the primary CRC was not associated with OS in the univariate analysis ( p = 0.965). Some previous studies have demonstrated that SUV max of the primary tumor may affect CRC prognosis 26 , 27 ; other studies have reported that PET/CT parameters are not associated with either disease-free survival or OS 28 30 . These discrepancies in findings may be because of the variability in tumor SUV measurements, confounded by tumor-associated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the prognostic role of MTV and TLG in patients with colorectal cancer 21,22,24,26 , but they showed contradictory results on the correlation between the metabolic parameters and cancer prognosis. Deantonio et al 26 evaluated the prognostic value of the metabolic parameters on 18 F-FDG PET for prediction of neoadjuvant chemoradiotherapy response and prognosis in patients with rectal cancer but did not nd any correlation with DFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the prognostic role of MTV and TLG in patients with colorectal cancer 21,22,24,26 , but they showed contradictory results on the correlation between the metabolic parameters and cancer prognosis. Deantonio et al 26 evaluated the prognostic value of the metabolic parameters on 18 F-FDG PET for prediction of neoadjuvant chemoradiotherapy response and prognosis in patients with rectal cancer but did not nd any correlation with DFS and OS. Another study with 18 F-FDG PET reported that high MTV and TLG were signi cantly associated with shorter OS and DFS on univariate analysis, while multivariate Cox proportional hazards analysis revealed that MTV and TLG were not signi cant potent predictors of DFS and OS 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AUC for focal neurology Youngs modulus + degree = 0.78Single centreStenting, coronary bypass surgeryPlaque density, vessel luminal diameterQCoronary artery stenosisRisk of plaque rupture; risk of significant cardiac ischaemia, infarction, deathNo luminal narrowing but with coronary artery calcium (CAC) score > 0 had a 5-year mortality HR 1.8 compared with those whose CACS = 0. No luminal narrowing but CAC ≥ 100 had mortality risks similar to individuals with non-obstructive coronary artery disease [138]CT angiography significantly better at predicting events than stress echo/ECG [68]Coronary death/non-fatal myocardial infarction was lower in patients with stable angina receiving CT angiography than in the standard-care group (HR = 0.59) [69]MulticentreMulticentreMulticentreStatins, stenting, coronary bypass surgery 18 F-NaSQAortic valve diseaseCoronary plaque [139]Acute events from abdominal aortic aneurysmValve stenosis presentLikelihood of plaque ruptureLikelihood of aneurysm ruptureReproducibility NaF uptake 10% [140]Baseline 18F-NaF uptake correlated closely with the change in calcium score at 1 year [141] 18 F-NaF uptake (maximum tissue-to-background ratio 1·90 [IQR 1.61–2.17]) associated with ruptured plaques and those with high-risk features [142]Aneurysms in the highest tertile of 18 F-NaF uptake expanded 2.5× more rapidly than those in the lowest tertile and were 3× more likely to rupture [143]SingleMulticentreCoronary stenting, aneurysm stentingMTRQMultiple sclerosisDisease progressionMTR significantly correlates with T2 lesion volume [144]Grey matter MTR histogram peak height and average lesion MTR percentage change after 12 months independent predictors of disability worsening at 8 years [145]Change in brain MTR specificity 76.9% and PPV 59.1% for Expanded Disability Status Scale score deterioration [146]MulticentreSingle centreSingle centreTiming of therapeutic interventionMalignant disease 18 FDG-SUV QCancerOesophageal cancerGood or poor prognosis tumour in terms of PFS and OSWide variation between individuals and tumours [147]Oesophageal cancer HR 1.86 for OS, 2.52 for DFS [148]Meta-analysisNeoadjuvant or adjuvant therapy or treatment modality combinations 18 FLT-SUVQCancerHigh proliferative activity presentSizeable overlap in values with normal proliferating tissues [75]Review of data from single centre studiesNeoadjuvant or adjuvant therapy or treatment modality combinations ADC MRF (ADC, T1 and T2)QQQCancer, correlates with tumour gradeR...…”
Section: Selecting and Translating Appropriate Imaging Biomarkers To mentioning
confidence: 99%